Electrical and electronic waste in Basic Education: Analysis of article production between 2008 and 2018 - Peixoto, Anyelle da Silva Pereira (2020)
Technological development in contemporary society brings, as a consequence, the issue of consumption and disposal of electronic equipment. In recent years, many studies have intensified, in this direction; these studies corroborate STS education, which has student citizenship training as one of its principles. To this end, it proposes discussions on the social and environmental impacts related to science and technology. This article is an excerpt from a bibliographic review of a dissertation from the Professional Master’s Program of the Graduate Program in Teaching Natural Sciences and Mathematics at the Federal University of Rio Grande do Norte. The objective is to analyze how the issue of Electronic Waste (e-waste) has been addressed in Basic Education, considering the period from 2008 to 2018. Thus, we sought to discuss the nature of the work; on the production, consumption, disposal and management of REE; and if possible alternatives are contemplated in the classroom. For the treatment of the data, elements of the content analysis of Bardin (2011) were used. The results showed that the topic has not been widely considered in Basic Education, in total, twenty-three publications were found. The disposal of these residues has been the main concern of the research analyzed. In addition, obsolescence and the influence of the media are perceived as motivating to consumption. It is noteworthy that the exercise of citizenship is subsidized by scientific knowledge, therefore, discussing about scientific and technological advances and their implications in society, are relevant.